2018
DOI: 10.1002/dc.23966
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and cellularity yield of reverse bevel versus fork‐tip fine needle biopsy

Abstract: Although we observed no difference in the diagnostic yield using either the fork-tip or the reverse bevel needle, the fork-tip needle had significantly better performance with regards to achieving more adequate cytologic specimen in fewer number of passes while at the same time requiring fewer episodes of ROSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…Finally, 24 studies 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 with 6641 patients were included in the meta-analysis. Main characteristics of included studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 24 studies 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 with 6641 patients were included in the meta-analysis. Main characteristics of included studies are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The number of passes was excluded from the model as this covariate did not provide a relevant contribution (pooled effect 0.14, 95% CI -0.46 to 0.75, p-value 0.638) and was missing for six studies [41,43,46,91,116,118]. After sensitivity analysis, two studies with a disproportionate influence were excluded ( Figure 11, supplementary fiIe) [47,77].…”
Section: Meta-regression Analysismentioning
confidence: 99%
“…After sensitivity analysis, two studies with a disproportionate influence were excluded (Fig. 9 s) [47,77].…”
Section: Meta-regression Analysismentioning
confidence: 99%
“…Recent studies, mainly those focusing on solid pancreatic masses only, achieved a diagnostic accuracy of 86%–96.5%. [ 6 14 15 21 25 31 32 ] The present study was not limited to solid pancreatic masses but included all patients referred for pancreatic EUS-FNB including cystic and benign lesions, where a precise diagnosis was needed for optimal patient management. As cystic lesions tend to offer less opportunity to obtain an adequate biopsy as there often only are limited solid areas such as thickened cyst wall or mural nodules suitable for biopsy compared to solid pancreatic masses, the higher proportion of cystic compared to only including solid lesions may, at least in part, explain the slightly lower accuracy in the present study (85.6%).…”
Section: Discussionmentioning
confidence: 99%